2020
DOI: 10.1002/mame.202000107
|View full text |Cite
|
Sign up to set email alerts
|

Perpendicular and In‐Plane Conductivity of Poly(methyl methacrylate) Composite Films Filled with Carbon‐Based Fillers Prepared from Solution Casting Process

Abstract: In this study, poly(methyl methacrylate) (PMMA)/carbon black (CB), PMMA/carbon fiber (CF), and PMMA/carbon nanotube (CNT) conductive composite films with different filler concentrations are prepared using the solution casting technique. Both perpendicular and in‐plane direction conductivity of all the binary composite films are investigated, percolation thresholds (ϕc) of both directions of PMMA/CB, PMMA/CF, and PMMA/CNT composite films are investigated and the experimental data are fitted using McLachlan’s eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Flexible conductive composites can be prepared by dispersing a certain amount of carbon nanotubes (CNTs) in the flexible polymer matrix. [1][2][3][4][5][6][7][8][9][10][11][12][13] Under the conditions of temperature change and strain, the resistance of CNT conductive network in the composites will change correspondingly, which reflects the temperature sensitivity [14] and stress sensitivity. [15,16] Therefore, the composite material can be applied to intelligent wearable electrics, [17,18] multifunctional sensors, [19][20][21] and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible conductive composites can be prepared by dispersing a certain amount of carbon nanotubes (CNTs) in the flexible polymer matrix. [1][2][3][4][5][6][7][8][9][10][11][12][13] Under the conditions of temperature change and strain, the resistance of CNT conductive network in the composites will change correspondingly, which reflects the temperature sensitivity [14] and stress sensitivity. [15,16] Therefore, the composite material can be applied to intelligent wearable electrics, [17,18] multifunctional sensors, [19][20][21] and other fields.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the conductivities in different measuring directions can be different, which often results from the orientation of conductive fillers [34][35][36][37][38][39]. Studies including perpendicular (through-thickness) electrical conductivity mainly focus on the following few categories: (1) Methods of enhancing perpendicular conductivity of carbon fiber reinforced polymer composites to minimize their damage from lightning strikes [40][41][42].…”
Section: Introductionmentioning
confidence: 99%